Physical Simulation of the Water-Conducting Fracture Zone of Weak Roofs in Shallow Seam Mining Based on a Self-Designed Hydromechanical Coupling Experiment System - Hao Zha; Weiqun Liu; Qinghong Liu (Geofluids)
Due to inappropriate mining practices, water-conducting fracture zones can develop in an aquifer, not only destroying the surface-water environment but also causing water inrush, even hurting or killing workers. To avoid such disasters, investigating and simulating the evolution mechanism of water-conducting fractures are becoming a research focus in mining engineering, especially regarding the organisation and development of fractures. Our work mainly involved the design of low-strength analogous materials and the simulation of fracture evolution for weak-roof problems in shallow seam mining based on a self-built experimental hydromechanical coupling system. The experimental results show that the vertical stress in the roof increases first as the working face approaches and finally decreases to near its initial value as the working face passes. The relationship between fracture depth and coal-seam excavation distance is obviously nonlinear. The leakage velocity of surface water remains stable in the early stage of excavation and increases when the fracture develops through the main aquifuge. The maximum fracture depth is 76.18 m for the Yili coal mine with weak roofs and shallow coal seams. In addition, we numerically simulated and verified the evolution patterns with the FLAC3D platform. The simulated fracture depth of the Yili coal mine agreed with the in situ borehole observation very well and was more accurate than the output of the empirical formula. Our work provides new methods and relevant data for research on the evolution of water-conducting fractures in weak roofs during shallow seam mining.